ANALISIS PENGARUH BANGKITAN PERJALANAN PENDUDUK TERHADAP KINERJA JALAN UTAMA KAWASAN PERUMAHAN WIRA PRAJA MUARA TEWEH - Akhmad Abdi Damhudi (Lambung Mangkurat University Press, 2015)
The aim of this research is to analyze the effect of the residents’ trip toward the performance of the region's main road in Wira Praja Housing complex in Muara Teweh. The aspects being analyzed in this research are the model of residents trip as the independent variable (x), the number of family members who go to work form home (x1), the number of family members who are students (x2), the number of family members who do not work or are not students (x3), household size based on the site of the family (x4), the number of car ownerships in units of vehicles (x5), the number of motorcycle ownerships in units of vehicles (x6), the number of bicycle ownerships (x7), total vehicle ownerships in the house (x8), total income per family per month in ten thousand rupiahs (x9), the types of house (between 36 and 45, 45 and 60, and bigger than 60) (x10), and the dependent variable (y) which is the total trips per family per day, and how the residents’ trip influences the performance of the road on the existing conditions. From the data, a forecasting is made for the next 5years.The research result shows the relationship between the number of trips (total trips) in the area of Wira Praja Housing of Muara Teweh as the dependent variable (y) and as the independent variable (x). The best regression model for the prediction of the trip is y = 1,014 + 0,441x8+ 0,004x9.The contribution of vehicles to the traffic on the main road of Wira Praja Housing Complex in Muara Teweh is grouped based on types of vehicles during traffic’s peak hour traffic. The composition of vehicles at peak hours showed that MC contributes 93% and LV contributes 7% to the traffic during peak hours.Each point of observation of residents’ trip shows an existing degree of saturation. On Jl. Wira Praja towards Jl. Pendreh observation point DS1= 0.142, on Jl. Wira Praja towards Jl. Pendreh and Jl. Ronggolawe observation point DS2 = 0.135, and on Jl. Wira Praja towards Jl. Ronggolawe observation point DS3 = 0.143. Based on the regulation (Permenhub No. 14 Year 2006), it is obtained the degree of saturation are sufficient (≤ 0.35), the level of service isA.The assessment of traffic forecasting for the next 5 years is assumed from the assessment of the Wira Praja Housing Complex Muara Teweh, traffic flow outside the housing and the traffic flow taken from the planned educational zones in residential areas. Forecasting is done with a few assumptions of housing development, namely 37, 100, 200, 300, 400, and 500 housing units. To forecast the traffic assessment from all assumption, it is found that the greater the assumptions of the housing development is, the higher the DS value of each point of observation will be.